Enhancing quality and equity in depressed, deprived and underserved (DDU) urban schools the Philippine study - Elloso, Julian E.
This study conducted in four depressed, deprived and underserved (DDU) elementary school in Metro Manila aimed at understanding the impact of within-school quality and equity among students and finding out differences among schools with similar resources. Results show that: 1) there is uniform pattern of teaching in all schools; 2) teachers generally feel negative about most of their pupils; and 3) educational leadership is usually viewed as resource generation for the school's physical environment.
Keywords: Elementary schools -- Philippines -- Manila Metropolitan Area -- Evaluation; School management and organization -- Philippines -- Manila Metropolitan Area